3D object detection based on synthetic RGB image. (15th February 2021) - Xu, Chao; Li, Zeshen; Jiang, Du; Yun, Juntong; Liu, Ying; Liu, Yibo; Bai, Dongxu; Ying, Sun
With the rapid development of computer vision technology and the maturity of 2D object detection technology, 3D object detection has attracted more and more attention of scholars. As an extension of 2D object detection, 3D object detection can not only detect the object category and position in the image, but also output the spatial position and pose angle of the object in a certain 3D coordinate system. It has a considerable application prospects in automatic driving, robot operation and augmented reality. However, 3D object detection is much more difficult than 2D object detection, and it is very difficult to make and label the data set, which has high hardware requirements. At present, there is no dominant algorithm, and scholars use a variety of methods. In order to solve the above problems, this paper proposes a method of making and synthesising 3D object detection data sets. Based on the improved 2D object detection algorithm, 3D object detection of single RGB image is realised.